Cotrimoxazole-Induced Hypoglycemia in an HIV-Infected Patient - Christine A Hughes; Constance L Chik; Geoffrey D Taylor (Canadian Journal of Infectious Diseases)
A case of cotrimoxazole-induced hypoglycemia is described in a male patient infected with HIV. Ten days after initiating high dose cotrimoxazole for suspected Pneumocystis carinii pneumonia, the patient developed neuroglycopenic symptoms and diaphoresis. Blood glucose levels were repeatedly low, with elevated insulin and C-peptide levels despite multiple intravenous bolus doses and infusions of dextrose. Hypoglycemia resolved after approximately 36 h of treatment with dextrose and discontinuation of cotrimoxazole. A review of reported cases of hypoglycemia associated with cotrimoxazole is provided, including information about onset, risk factors and possible mechanism.